1998
DOI: 10.1086/305288
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Hot Stellar Population of the Globular Cluster ω Centauri

Abstract: We analyze the far-UV and Stro mgren u photometric data of the globular cluster u Cen presented in an earlier paper. The color-magnitude diagram of the cluster from these two bands shows that u CenÏs horizontal-branch (HB) consists of a group of cooler intermediate blue HB (IBHB) and a group of extreme HB (EHB) stars, together with a large population of post-HB stars. Unexpected features in the diagram are a discontinuity between the EHB and IBHB objects lying at an, unusually large population of stars below t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 40 publications
(1 reference statement)
1
55
2
Order By: Relevance
“…As shown in Figure 16d, if the blue-hook stars have envelopes with the normal cluster abundances, the blue-hook stars pile up near the end of the canonical ZAHB, with no gap between the canonical EHB and blue-hook stars. Whitney et al (1998) argued that such an e †ect could explain the gap between the EHB and BHB in u Cen. They only considered blue-hook stars with normal atmospheres, and showed that the range of giving rise to the blue-hook stars was larger g R than the range of populating the HB between the EHB g R and BHB ; this e †ect would be exaggerated for the more metal-rich component of the u Cen metallicity distribution (see DÏCruz et al 1996).…”
Section: Ehb Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 16d, if the blue-hook stars have envelopes with the normal cluster abundances, the blue-hook stars pile up near the end of the canonical ZAHB, with no gap between the canonical EHB and blue-hook stars. Whitney et al (1998) argued that such an e †ect could explain the gap between the EHB and BHB in u Cen. They only considered blue-hook stars with normal atmospheres, and showed that the range of giving rise to the blue-hook stars was larger g R than the range of populating the HB between the EHB g R and BHB ; this e †ect would be exaggerated for the more metal-rich component of the u Cen metallicity distribution (see DÏCruz et al 1996).…”
Section: Ehb Gapmentioning
confidence: 99%
“…In this paper, we present a new theoretical scenario for understanding these peculiarities of the EHB population in NGC 2808, as well as u Cen. DÏCruz et al (2000) and Whitney et al (1998) claimed that the hot subluminous stars on the HB of u Cen were probably a population of "" blue-hook ÏÏ HB stars. These are stars that experience a late helium-core Ñash.…”
Section: Introductionmentioning
confidence: 99%
“…This GC has at least three separate, well-defined red giant branches (RGBs), an extended HB morphology, and a large number of subluminous extreme HB stars (e.g., D'Cruz et al 1996D'Cruz et al , 2000Whitney et al 1998;Pulone et al 1998;Pancino et al 2003;Rey et al 2004;Freyhammer et al 2005;Cassisi et al 2009;Bellini et al 2009;Calamida et al 2009Calamida et al , 2010. Hubble Space Telescope (HST) observations have also uncovered a triple MS (Bedin et al 2004;Bellini et al 2009Bellini et al , 2010, in addition to at least four SGBs (Villanova et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The late-hot-flash model has been used to explain the existence of blue-hook stars found in several massive GCs (Whitney et al 1998;D'Cruz et al 2000;Brown et al 2001). In our calculations, however, we did not consider the helium-flash mixing process.…”
Section: Resultsmentioning
confidence: 99%